DEVELOPMENT OF THE EDUCATIONAL PROGRAM OF THE SECOND (MASTER’S) LEVEL OF HIGHER EDUCATION IN THE FIELD OF KNOWLEDGE 22 HEALTHCARE SPECIALTY 226 PHARMACY, INDUSTRIAL PHARMACY SPECIALIZATION 226.01 PHARMACY BASED ON THE NEW STANDARD OF HIGHER EDUCATION - Shapovalov Валентин; Shapovalova Вікторія; Osyntseva Аліна; Nehretskii Сергій; Derkach Анатолій; Sichkarenko Олександр (Actual Problems of Medicine and Pharmacy, 2023)
Institutions of higher education for training masters of the second level of higher education in the field of knowledge 22 Healthcare, specialty 226 Pharmacy, industrial pharmacy, specialization 226.01 Pharmacy from the 2023/2024 academic year must be guided by the new Higher Education Standard. Determined that the Standard provides differences for specializations in the field of pharmacy. The study contains information on the compliance of the competencies defined by the Standard with the descriptors of the National Qualifications Framework and the compliance of the learning outcomes and competencies defined by the Standard. An example of the project of the second (master's) level educational program developed by the authors of the article was given.